Asymmetric Synthesis of Hydrocarbazoles Catalyzed by an Octahedral Chiral‐at‐Rhodium Lewis Acid. Issue 12 (7th September 2015) - Huang, Yong; Song, Liangliang; Gong, Lei; Meggers, Eric
Abstract: A bis‐cyclometalated chiral‐at‐metal rhodium complex catalyzes the Diels–Alder reaction between N ‐Boc‐protected 3‐vinylindoles (Boc= tert ‐butyloxycarbonyl) and β‐carboxylic ester‐substituted α, β‐unsaturated 2‐acyl imidazoles with good‐to‐excellent regioselectivity (up to 99:1) and excellent diastereoselectivity (>50:1 d.r.) as well as enantioselectivity (92–99 % ee ) under optimized conditions. The rhodium catalyst serves as a chiral Lewis acid to activate the 2‐acyl imidazole dienophile by two‐point binding and overrules the preferred regioselectivity of the uncatalyzed reaction. Abstract : New Diels : A bis‐cyclometalated chiral‐at‐metal rhodium‐based Lewis acid catalyzes the asymmetric Diels–Alder reaction between N ‐Boc‐protected 3‐vinylindoles and β‐carboxylic ester‐substituted α, β‐unsaturated 2‐acyl imidazoles and overrules the preferred regioselectivity of the uncatalyzed reaction.